Saturday

March 28, 2015

March 28, 2015

Posted by **Lost One** on Tuesday, February 26, 2013 at 12:10pm.

- Calc -
**Steve**, Tuesday, February 26, 2013 at 2:44pmy =(x+3)^3 / √(x^2 -1)

lny = 3ln(x+3) - 1/2 ln(x^2-1)

1/y y' = 3/(x+3) - x/(x^2-1)

1/y y' = (3(x^2-1) - x(x+3))/((x+3)(x^2-1))

1/y y' = (2x^2-3x-3)/((x+3)(x^2-1))

y' = (x+3)^3 / √(x^2 -1) * ((2x^2-3x-3)/((x+3)(x^2-1)))

= ((x+3)^2 * (2x^2-3x-3))/(x^2-1)^(3/2)

**Answer this Question**

**Related Questions**

Calc - Compute the derivative of f(x)=5^x^2+1 using logarithmic differentiation.

calc - find the derivative of y = sqrt(9 - 16x) Use the chain rule. First find ...

calc - find derivative using limit definition: f(x) = x - sqrt(x) so f'(x) = lim...

calc - Use logarithmic differentiation to find the derivative of the function. y...

calc - logarithmic differentiation of find derivative of y= square root of x^x

Calculus 1 - Use logarithmic differentiation to find the derivative of the ...

Calc I - if f(t)=sqrt(4t+1) find f''(2) I got the first derivative to be: 1/2(4t...

Calc - Can anyone help me find the derivative of these functions? y = x^2x y = x...

finding c: calc - let f(x)=square root x. if the rate of change of at x=c is ...

Calculus - 1.) Find the derivative of tan (sec x). 2.) Find the derivative if 1/...